PENYISIPAN TANDA AIR PADA CITRA DIJITAL BERBASIS DEKOMPOSISI NILAI SINGULIR (DNS) - Basaruddin, T; Cahyana, Cahyana (UI Scholars Hub, 2006)
Imperceptible of Watermarking in Digital Image Based Singular Value Decomposition. Watermarking is a commonly used technique to protect digital image from unintended used such as counterfeiting. This paper will address one of the techniques to embed a watermark to digital image which is based on the singular value decomposition. The primary target to be achieved by a good watermarking technique is that the watermarked image is imperceptible and that the inserted image can still be perfectly retrieved even though various transformations are done to the watermarked image. Our works show that the SVD-based watermarking demonstrates both imperceptibility as well as robustness of the watermarking scheme as indicated by significantly high value of correlation between the inserted and retrieved logo after some transformation such as PSNR, RML and Compression.